An asset pricing model that captures all the proper factors which affect the price of an asset seems to be a far-off reality according to the evidence of the existing ones. - Karousios, Konstantinos (2007)
This dissertation will be a literature review of four asset pricing models, discussing their structure, their achievements, as well as their weaknesses. These models are the capital asset pricing model (CAPM), the three-factor model of Fama and French, the liquidity-augmented capital asset pricing model and the behavioural asset pricing model. The first three models are derived from the standard finance theory and the latter is derived from the behavioural finance theory. The research question is whether an asset pricing model that captures all the proper factors which affect the price of an asset is feasible according to the evidence of the existing ones. The literature review on this topic, documents the inability of the existing asset pricing models to capture all the proper factors that affect the price of an asset.